Essential role of ubiquitin-specific protease 8 for receptor tyrosine kinase stability and endocytic trafficking in vivo. - Niendorf, S; Oksche, A; Kisser, A; Löhler, J; Prinz, M; Schorle, H; Feller, S; Lewitzky, M; Horak, I; Knobeloch, K (2007)
Posttranslational modification by ubiquitin controls multiple cellular functions and is counteracted by the activities of deubiquitinating enzymes. UBPy (USP8) is a growth-regulated ubiquitin isopeptidase that interacts with the HRS-STAM complex. Using Cre-loxP-mediated gene targeting in mice, we show that lack of UBPy results in embryonic lethality, whereas its conditional inactivation in adults causes fatal liver failure. The defect is accompanied by a strong reduction or absence of several growth factor receptor tyrosine kinases (RTKs), like epidermal growth factor receptor, hepatocyte growth factor receptor (c-met), and ERBB3. UBPy-deficient cells exhibit aberrantly enlarged early endosomes colocalizing with enhanced ubiquitination and have reduced levels of HRS and STAM2. Congruently immortalized cells gradually stop proliferation upon induced deletion of UBPy. These results unveil a central and nonredundant role of UBPy in growth regulation, endosomal sorting, and the control of RTKs in vivo.